Nutritional Value of Mulberry (Morus alba) Forage Harvested During Dry and Wet Seasons in Northern Ethiopia - Ebrahim, Assen; Animut, Getachew; Urge, Mengistu; Hailemichael, Aklilu (Indian Journal of Animal Nutrition, 2018)
This study was conducted to evaluate the chemical composition, in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD) and in sacco DM and nitrogen (N) degradability of leaves and edible branches of mulberry harvested in dry and wet seasons. In sacco DM and N degradability were evaluated using three rumen fistulated crossbred steers (Boran Ã— Friesian). The contents of CP, total ash and NDF contents of mulberry were influenced (P